Spatial and resource development in creating a quality framework for the urban environment of the Donetsk People's Republic - Igor Vladimirovich Kushchenko; Valentin Valentinovich Volgin (Недвижимость: экономика, управление, 2023)
At the time of the actual collapse of Ukraine in 2014, the Donetsk and Lugansk regions together provided about 18 % of all industrial production in Ukraine, and the share of Donbass in the sale of industrial products of the country was higher than any other region.